THE EFFECT OF BOARD SIZE, PROFITABILITY AND CAPITAL INTENSITY ON TAX AGGRESSIVENESS IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2017 - 2019 - Taniya Fatimah Becik; Nuramalia Hasanah; Indah Muliasari (Transpublika Publisher, 2023)
The Indonesian property and real estate sector refers to the industry involved in the development, sale, purchase, and management of properties, including residential, commercial, and industrial real estate. This sector is significant in the Indonesian economy due to its contributions to employment, investment, and economic growth. This study aims to comprehensively examine the impact of board size, profitability, and capital intensity on tax aggressiveness within the context of the Indonesian property and real estate sector. Employing a quantitative approach, the research utilizes multiple linear regression analysis with Eviews software version 12 to analyze data from 60 entities in the sector listed on the Indonesian stock exchange from 2017 to 2019. The findings reveal intriguing insights. Board size is found to exert a discernible influence on tax aggressiveness, emphasizing the role of corporate governance in shaping tax strategies. However, the study challenges conventional assumptions by demonstrating that profitability does not significantly impact tax aggressiveness. In contrast, capital intensity emerges as a significant determinant of tax aggressiveness, highlighting the role of financial structure in tax planning decisions. These findings contribute to the understanding of the intricate relationship between corporate governance, financial metrics, and tax strategies in the examined sector. The research underscores the importance of nuanced decision-making in tax planning, acknowledging the varying impacts of different variables. By providing empirical evidence, this study offers valuable insights for practitioners and policymakers aiming to enhance tax strategy effectiveness and transparency.